2011
DOI: 10.1186/1475-2875-10-155
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of uncomplicated malaria at public health facilities and medicine retailers in south-eastern Nigeria

Abstract: BackgroundAt primary care facilities in Nigeria, national treatment guidelines state that malaria should be symptomatically diagnosed and treated with artemisinin-based combination therapy (ACT). Evidence from households and health care providers indicates that many patients do not receive the recommended treatment. This study sought to determine the extent of the problem by collecting data as patients and caregivers leave health facilities, and determine what influences the treatment received.MethodsA cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 24 publications
8
80
4
Order By: Relevance
“…The study by Mangham et al in 2009, about five years after policy change in the same area suggested utilization rate of 24.2% for ACT in medicine outlets using patients’ exit questionnaires [2]. Findings corroborate the results of previous, related studies in the area in terms of availability and utilization of anti-malarial drugs [2,5,6,8]. Prescriptions were mostly adults, while children cases were limited, comprising prescriptions from hospitals.…”
Section: Discussionsupporting
confidence: 69%
“…The study by Mangham et al in 2009, about five years after policy change in the same area suggested utilization rate of 24.2% for ACT in medicine outlets using patients’ exit questionnaires [2]. Findings corroborate the results of previous, related studies in the area in terms of availability and utilization of anti-malarial drugs [2,5,6,8]. Prescriptions were mostly adults, while children cases were limited, comprising prescriptions from hospitals.…”
Section: Discussionsupporting
confidence: 69%
“…This is of particular concern for simultaneous absence of all four AL packs which precludes effective treatment and is likely to be associated with increased childhood mortality as shown in Western Kenya [11]. Yet, ACT stock-outs revealed in our study are not unique reports – they had been reported from Uganda [12], Zambia [13], Nigeria [14], Sudan [15], Tanzania [16], Senegal [17], and indeed in the previous smaller studies in Kenya [10]. Similarly to AL availability, no significant changes were observed during 2010 in the capacity of health facilities to provide parasitological diagnosis resulting in an overall gap of 42% of facilities unable to provide either malaria microscopy or RDT diagnostic services.…”
Section: Discussionmentioning
confidence: 65%
“…The data suggest an association between the use of ACTs for positive mRDTs and baseline preferences for, or use of, ACTs rather than other antimalarials. For example, in Nig1, where ACT use was generally low, prior to the intervention, other antimalarials were asked for by patients, prescribed and purchased more commonly than ACTs 34. In contrast, in Tanz1, where adherence to RDT positive results was higher, according to stakeholder interviews, ACTs were patients' preferred antimalarial.…”
Section: Resultsmentioning
confidence: 99%